Gambaran Pengetahuan Mahasiswa S1 Keperawatan Tentang Kewaspadaan Standar Berdasarkan 5 Moment Hand Hygiene Dalam Pencegahan dan Pengendalian Infeksi - Manullang, Stevent Alexander; Boyoh, Debilly Yuan (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
Nosocomial infection is a disease that is often found in patients during treatment, and is the biggest problem in every hospital. A WHO study showed that 8.7% of 55 hospitals from 14 countries in Europe, the Middle East, Southeast Asia and the Pacific had nosocomial infections and 10% in Southeast Asia. Infections can be transmitted in many ways, including through contact, transmission through inanimate objects that have been contaminated by germs, respiratory transmission. Understanding when to wash hands can make it possible to break the chain of transmission mentioned. Adhering to recommended infection prevention measures can be a relatively inexpensive strategy, especially hand hygiene and sanitation and the wearing of gloves. The research design that will be used in this study is quantitative with quantitative descriptive method. This study is to see an overview of the level of knowledge of students about the 5 moments of hand hygiene. The sampling technique used was total sampling. The results of the study: the level of knowledge of respondents was in the good category of 42 people (89.4%), knowledge in the sufficient category amounted to 5 people (10.6%), with statement items that were answered correctly with the largest frequency of 46 (rank 1 reads: